How People’s Daily frame aerospace issue (1975-2023) - Li, Hui; Sharon Wilson; Noor Azmira Mohamed (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study examines how People’s Daily, the party-affiliated newspaper of the Communist Party of China (CPC), has framed aerospace issues from 1975 to 2023, constructing narratives that serve its political and ideological goals in shaping public opinion. Aiming to uncover the dominant frames used in five periods and analyse their evolution in relation to China’s political leadership and national goals, the study uses methodologies that combine inductive and deductive framing analysis to reconstruct dominant frames from a sample of 145 articles (from a sample population of 4,706). The study identifies six dominant frames: Space Race, Independently-develop Aerospace Projects, Dynamic Aerospace Development, Aerospace Achievement-Orientated, International Cooperation, and Nation-Building. These frames are traced across five generations of CPC leadership, revealing a discursive evolution from early portrayals of survival and international competition to narratives positioning China as a leading global space power. In the later periods, the framing increasingly ties aerospace advancements to China’s historic dream of flight and national rejuvenation. A critical discourse analysis (CDA) further reveals the framing strategies and narratives of People’s Daily contribute to reinforcing the legitimacy of the CPC, cultivating a heightened sense of nationalism, and gaining public backing for extensive social transformation. The findings suggest that People’s Daily does not merely report on aerospace issues but actively induces its target audience to accept the interpretation of aerospace developments as symbols of national building and rejuvenation, socialist modernity, and the CPC’s governance efficacy.